2021
DOI: 10.1192/bjo.2021.1041
|View full text |Cite
|
Sign up to set email alerts
|

Personal, social and relational predictors of UK postgraduate researcher mental health problems

Abstract: Background Emerging evidence demonstrates that postgraduate researchers have high rates of mental health problems. These problems are distressing, affect PhD studies, and have longer-term potential effects beyond the duration of the PhD. Yet large-scale studies of multiple risk and protective factors are rare. Aims We aimed to test the predictive validity of a comprehensive set of potential determinants of mental health symptoms (depression, anxiety and suicidality) among postgraduate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…This study has revealed a correlation between educational level and mental disorders. Postgraduate and PhD students faced additional stress in managing research tasks and experimental projects, with unexpected closures and disruptions impeding progress [ 27 , 28 ]. Delays in graduation and weakened competitiveness in the job market exacerbated their mental health challenges [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has revealed a correlation between educational level and mental disorders. Postgraduate and PhD students faced additional stress in managing research tasks and experimental projects, with unexpected closures and disruptions impeding progress [ 27 , 28 ]. Delays in graduation and weakened competitiveness in the job market exacerbated their mental health challenges [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the unsurprising importance of social support in combating distress that can arise either from loneliness and isolation of doctoral work, and from being too enmeshed in it (Berry et al, 2021), was reiterated in our interviewees' reports, as was the apparently beneficial effect of belonging to multiple social groups (Iyer et al, 2009) that one could switch between, creating a level of distance and separation, even if -or especially if, contrary to Iyer and colleagues' findings -the multiple identities did not always have to be compatible and mutually reinforcing. The reports in our study also seem to support another of Berry et al's (2021) findings about the detrimental effect of too many social roles within the context of academia (researching, teaching, etc.)…”
Section: Discussion and Directions For Further Researchmentioning
confidence: 99%
“…For those for whom such validation -as well as the practical opportunity for networkingwas lacking on a regular basis, the experience of doctoral research could become adversely affected by maladaptive perfectionism, recognised by Berry et al (2021) as one of the chief contributors to ill mental health among doctoral students. In the words of one of the (externally funded) interviewee: "You start a PhD and it's like permanent sense of incompetence.…”
Section: What's An Academic? Some Observations On Social Category Mea...mentioning
confidence: 99%
“…Poor mental health has been identified as a central issue for doctoral students in the United Kingdom (UK) [1,2], Europe [3], and internationally [4]. Recent research has indicated a high prevalence of stress [5], psychological distress [6,7], and depression and anxiety [8] in doctoral students at UK universities. Poor resilience to stress has been identified in this population [9][10][11], which also contributes to poorer mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%